WOMEN-WRITERS IN ENGLISH LITERATURE - Erkinov Adham Anvar o'g'li , (TADQIQOTLAR.UZ, 2024)
ABSTRACT Women writers have played a significant role in shaping English literature throughout history. From the Brontë sisters to Virginia Woolf, women have made lasting contributions to the literary world. This article aims to explore the impact of women writers on English literature, considering their distinctive voices and perspectives. The Brontë sisters (Charlotte, Emily, and Anne) were prolific writers in the 19th century, known for their groundbreaking novels such as "Jane Eyre" and "Wuthering Heights." Virginia Woolf was a key figure in the modernist movement, known for her experimental writing style and feminist themes.